Influences of nutritional information on fast food purchasing behaviour among undergraduates at Universiti Sains Malaysia, Kubang Kerian, Kelantan - Salim, Nur Amalina (Universiti Sains Malaysia, 2016)
Eating out, especially at fast food restaurants is often regardless unhealthy option and related to health issues such as obesity. Nutritional information is often provided in many restaurants to allow customers to make informed choice. Thus, this study was carried out to determine the influences of providing nutritional information on fast food restaurant menu, especially among undergraduates at Universiti Sains Malaysia Health Campus, who often eat outside the campus during semester. This is quantitative study, where validated questionnaire adapted from previous study was used to determine the general perception on nutritional information, nutrient intake and purchasing intention when eating out. A total of 185 undergraduates participate from three different school, PPSP (n=54, 29.2%), PPSG, (n=54. 29.2%), PPSK (n=77, 41.6%) in USM, Health Campus. In general, majority of the undergraduates eat fast food at least once in a week (n= 105, 56.8%) and most of them prefer to eat outside on weekend (n=156, 84.3), and they consume fast food mainly as socialising event with friends. Majority perceived that it is importance to provide nutritional information at fast food restaurant (n=183, 98.9%). Mean for calorie, fat and sodium composition of their food choices were significantly different between before and after providing nutritional information of the food items on the food menu (p<0.001). Majority indicated that they were likely to purchase healthier food items when nutritional information w'as provided (n=159. 85.9%). There is no association between the usage of nutritional information and nutrient composition from food selected upon receiving the nutritional information (p>0.05).